(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2022)
Competition is very important for the success or failure of a company. Company competition to excel or achieve high performance by implementing strategies, aiming to achieve a profitable and strong position to stem competition in the industry. PT. Sanghiang Perkasa (Kalbe Nutritionals). During the current pandemic the company PT. Sanghiang Perkasa (Kalbe Nutritionals) Yogyakarta is planning a strategy to be able to survive in the face of competition with other business players and be able to increase product sales. To find out the marketing strategy of PT Sanghiang Perkasa in Increasing Product Sales. Methods: This study uses a descriptive qualitative type of research. Data collection techniques using interviews, observation and documentation. In this study, the analysis was carried out by describing the marketing strategy of PT Sanghiang Perkasa in increasing product sales. The position of PT Sanghiang Perkasa business sustainability strategy through a SWOT analysis is in quadrant I, with a strength of 0.5 (5%) and an opportunity of 0.4 (4%). This shows that strengths and opportunities are still below 50%, meaning that PT Sanghiang Perkasa has strengths and opportunities but is at a low point so that it requires an alternative strategy for PT Sanghiang Perkasa medium-term SO strategy. Strategies that can be applied include the Strength Opportunities (SO) strategy by maximizing the strengths and paying attention to market opportunities. An alternative strategy that can be applied by PT Sanghiang Perkasa after knowing its business marketing position is to maintain and improve the quality of products and services to consumers. Increased sales of PT. Sanghiang Perkasa indicates a good marketing performance, and of course it has a very positive effect on the survival of the company.